2020
DOI: 10.3389/fcell.2020.598205
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Is a Tumor Suppressor in Aggressive Endometrial Cancer Cells and Its Expression Is Regulated by miR-216a and lncRNA MEG3

Abstract: BackgroundPoorly differentiated endometrioid adenocarcinoma and serous adenocarcinoma represent an aggressive subtype of endometrial cancer (EC). Programmed death-ligand-1 (PD-L1) was known to exhibit a tumor cell-intrinsic function in mediating immune-independent tumor progression. However, the functional relevance of tumor cell-intrinsic PD-L1 expression in aggressive EC cells and the mechanisms regulating its expression remain unknown.MethodsPD-L1 expression in 65 EC tissues and 18 normal endometrium sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…Genome projects have shown that functional products encoded by the genome are not limited to proteins, but include a large number of biologically meaningful non-coding RNAs, such as miRNAs, circular RNAs (circRNAs) and lncRNAs (Anastasiadou et al, 2018;Yamamura et al, 2018). MiRNAs are known to target 3 -UTRs in mRNAs, thereby silencing gene expression at the post-transcriptional level (Anastasiadou et al, 2018;Yamamura et al, 2018;Xu et al, 2020). MiRNAs also interact with circRNAs and lncRNAs to regulate their stability (Anastasiadou et al, 2018;Yamamura et al, 2018).…”
Section: Mechanisms Of Piwil1 Dysregulation In Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Genome projects have shown that functional products encoded by the genome are not limited to proteins, but include a large number of biologically meaningful non-coding RNAs, such as miRNAs, circular RNAs (circRNAs) and lncRNAs (Anastasiadou et al, 2018;Yamamura et al, 2018). MiRNAs are known to target 3 -UTRs in mRNAs, thereby silencing gene expression at the post-transcriptional level (Anastasiadou et al, 2018;Yamamura et al, 2018;Xu et al, 2020). MiRNAs also interact with circRNAs and lncRNAs to regulate their stability (Anastasiadou et al, 2018;Yamamura et al, 2018).…”
Section: Mechanisms Of Piwil1 Dysregulation In Tumormentioning
confidence: 99%
“…MiRNAs also interact with circRNAs and lncRNAs to regulate their stability (Anastasiadou et al, 2018;Yamamura et al, 2018). Owing to their functions in the regulation of gene expression, noncoding RNAs regulate multiple biological processes, such as cancer (Anastasiadou et al, 2018;Yamamura et al, 2018;Xu et al, 2020). The expression of PIWIL1 could be regulated by different miRNAs at the post-transcriptional level.…”
Section: Mechanisms Of Piwil1 Dysregulation In Tumormentioning
confidence: 99%
“…The results of this meta-analysis confirmed that, in patients diagnosed with OPSCC, PD-L1 expression was associated with a better OS and PSF, but not with LRC. Notably, higher PD-L1 expression was correlated with improved OS rates in other tumor types, including melanoma ( 45 ), colorectal cancer ( 46 ), Merkel-cell carcinoma ( 47 ), and endometrial cancer ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Xu et al evaluated a total of 65 human EC tissues and 18 normal samples and showed that MEG3 downregulates the miR-216a expression, leading to increased expression of tumor suppressor PD-L1. Thus, it inhibits the EC cell migration and invasion [ 234 ].…”
Section: Lncrnas In Female-oriented Cancersmentioning
confidence: 99%